Reducing Environmental Pollution Through Behavioral Change and Education: A Repeated Cross-Sectional Pilot Study - Junu Shrestha; Ranju Karki; Esther A. Adewusi (Journal of Education in Science, Environment and Health)
This repeated cross-sectional pilot study examined the impact of environmental education on reducing overall waste generation among students enrolled in an environmental health course from Fall 2020 to Spring 2023. The data included trash generation, single-use plastic, and paper products. Each student logged their daily usage of these waste products in a standard spreadsheet. The data collection phases were divided into three behavioral change intervention timelines: Before-Intervention (BI-Week 1-5), Phase -1 (PH1I- Week 6-10), and Phase-2 Intervention (PH2I-Week 11-14). The study found a significant reduction in the use of grocery bags (p<0.001*), produce bags (p=0.03*), cutlery/straws (p=0.01*), paper towels (p<0.001*), toilet paper (p<0.001*), the weight (p=0.003*) and number(p=0.02*) of trash. The results indicated that the mean differences in waste such as paper towels p<0.001*(PH1I VSBI);p<0.001*(PH2I VS BI); p=0.009*(PH2I VS PH1I)], toilet paper [p=0.003*(PH1I VS BI); p=0.001*(PH2I VS BI); p<0.001*(PH2I VS PH1I)], grocery bags [p=0.001*(PH1I VS BI); p=0.001*(PH2I VS PH1I), Cutlery/Straw [p=0.006*(PH1I VS BI);p=0.007*(PH2I VS BI), and the average weight of trash bags [p=0.002* (PH1I VS BI); p=0.004*(PH2I VS PH1I)] were statistically significant after the interventions. Therefore, the study concluded that environmental awareness, self-accountability, and education are effective in controlling single-use plastic and paper products and reducing trash generation.